What Really Matters in Auction Design. - Klemperer, P (CEPR, 2000)
The most important issues in auction design are the traditional concerns of competition policy-preventing collusive, predatory, and entry deterring behaviour. Ascending and uniform-price auctions are particularly vulnerable to these problems (we discuss radiospectrum and football TV-rights auctions, electricity markets, and takeover battles), and the Anglo-Dutch auction - a hybrid of the sealed-bid and ascending auctions may often perform better. However, everything depends on the details of the context; the circumstances of the recent UK mobile-phone license auction made an ascending format ideal. We also discuss the current 3G spectrum auctions in Germany and the Netherlands. Auction design is a matter of 'horses for courses', not 'one size fits all'.